2007
DOI: 10.1002/micr.20357
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tamoxifen on arterial microvascular anastomosis

Abstract: Breast reconstruction after cancer treatment is based on the circulation of pedicle and microvascular flaps. This article aimed to verify the effect of tamoxifen (TMX) pretreatment in arterial anastomosis in rats. Twenty female Wistar rats were equally divided into two groups. TMX (0.3 mg/kg) was administered to the experimental group for 2 weeks orally. After this period, the right femoral artery was sectioned and a terminoterminal anastomosis performed. The same procedure was done in the control group, excep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…These finding may coincide with intimal hyperplasia, which has been observed within the arteries of rats treated with tamoxifen; this observation serves as a reminder that ERs are also located within the endothelium of arteries. 11 It is also known that the coronary and carotid vessels are at risk for atherosclerosis and thrombotic events from loss of estrogen exposure, and the internal mammary vessels—the most commonly utilized recipient vessels for microsurgical breast reconstruction—are in the direct vicinity of these vessels. However, it is unclear whether the use of tamoxifen would increase these risks for the internal mammary vessels and subsequently place microsurgical breast reconstruction at risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These finding may coincide with intimal hyperplasia, which has been observed within the arteries of rats treated with tamoxifen; this observation serves as a reminder that ERs are also located within the endothelium of arteries. 11 It is also known that the coronary and carotid vessels are at risk for atherosclerosis and thrombotic events from loss of estrogen exposure, and the internal mammary vessels—the most commonly utilized recipient vessels for microsurgical breast reconstruction—are in the direct vicinity of these vessels. However, it is unclear whether the use of tamoxifen would increase these risks for the internal mammary vessels and subsequently place microsurgical breast reconstruction at risk.…”
Section: Discussionmentioning
confidence: 99%
“…10 Moreover, in rats undergoing microsurgery, tamoxifen has been associated with increased intimal and total vessel wall thickness. 11 This finding prompted concerns that tamoxifen therapy at the time of microsurgical breast reconstruction may increase the risk of ischemia, vessel thrombosis, partial necrosis, and total flap failure.…”
Section: Introductionmentioning
confidence: 99%
“…Tamoxifen has been shown to stimulate platelet activation, 13 and animal studies have shown tamoxifen induces intimal hyperplasia and subsequently increases vessel wall thickness. 10 However, tamoxifen has also been demonstrated to have antithrombotic effects by inhibiting platelet activation. 14,15 Translating these observations toward defining the role of tamoxifen in anastomotic thrombosis is not straightforward.…”
Section: Discussionmentioning
confidence: 99%
“…We therefore also postulate the need for a prospective multi-center-study with a large amount of patiens that focuses on a few selected clinically significant variables. Due to the fact that vascular responsiveness to estrogen may differ significantly between various vascular locations, it seems that this study should also focus on only one region of flap origin, such as the abdomen (DIEP-, TRAM-, SIEP flaps) [8], [16]. …”
Section: Discussionmentioning
confidence: 99%
“…Therefore third generation aromatase inhibitors (AIs) have replaced Tamoxifen in the adjuvant therapy of hormone receptor-positive breast cancer [7]. De Pinho Pessoa et al showed a tamoxifen-induced intima hyperplasia in rats, and many clinical studies describe an increased risk for venous and arterial thrombosis under tamoxifen therapy [8], [9], [10], [11]. …”
Section: Introductionmentioning
confidence: 99%